mTOR inhibition improves fibroblast growth factor receptor targeting in hepatocellular carcinoma - Scheller, T (Br J Cancer, 2015)
BACKGROUND: Systemic therapy has proven only marginal effects in hepatocellular carcinoma (HCC) so far. The aim of this study was to evaluate the effect of targeting fibroblast growth factor receptor (FGFR) on tumour and stromal cells in HCC models. METHODS: Human and murine HCC cells, endothelial cells (ECs), vascular smooth muscle cells (VSMCs), hepatic stellate cells (HSCs), human HCC samples, FGFR inhibitor BGJ398 and mammalian target of rapamycin (mTOR) inhibitor rapamycin were used. Effects on growth, motility, signalling and angiogenic markers were determined. In vivo subcutaneous and syngeneic orthotopic tumour models were used. RESULTS: In tumour cells and ECs, targeting FGFR showed significant inhibitory effects on signalling and motility. Minor effects of FGFR inhibition were observed on VSMCs and HSCs, which were significantly enhanced by combining FGFR and mTOR blockade. In vivo daily (5 mg kg(−1)) treatment with BGJ398 led to a significant growth inhibition in subcutaneous tumour models, but only a combination of FGFR and mTOR blockade impaired tumour growth in the orthotopic model. This was paralleled by reduced tumour cell proliferation, vascularisation, pericytes and increased apoptosis. CONCLUSIONS: Targeting FGFR with BGJ398 affects tumour cells and ECs, whereas only a combination with mTOR inhibition impairs recruitment of VSMCs and HSCs. Therefore, this study provides evidence for combined FGFR/mTOR inhibition in HCC.